2009
DOI: 10.1007/s11695-009-9903-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy as Revisional Procedure for Failed Gastric Banding and Vertical Banded Gastroplasty

Abstract: Conversion of GB and VBG into LSG is feasible and safe. LSG is effective in the short term with a mean %EWL of 42.7% at 13.4 months. Long-term results of LSG as revisional procedure are awaited to establish its efficacy in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(38 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…The leak rate is reportedly higher after revision of AGB into SG -this procedure involves stapling over scarred tissue, a longer stapler line, and dissection at the left crus, which can jeopardize the blood supply at the gastroesophageal junction [24][25][26][27]. However, several studies have demonstrated SG's feasibility as a revision procedure [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The leak rate is reportedly higher after revision of AGB into SG -this procedure involves stapling over scarred tissue, a longer stapler line, and dissection at the left crus, which can jeopardize the blood supply at the gastroesophageal junction [24][25][26][27]. However, several studies have demonstrated SG's feasibility as a revision procedure [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…8,14,[19][20][21][22][23] Studies have shown that SG is safe and effective in achieving adequate weight loss in most patients. 24,25 We performed Roux-en-Y gastric bypass in one and SG in two patients with failed VBG. The polypropylene rings were removed to prevent occurrence of late inflammation in patients who were revised from VBG to SG.…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] Revision of LAGB High rates of failure in weight loss due to maladaptive eating, and band-related complications such as slippage, tubing leakage, esophageal motility disorders (and pseudo achalasia)are reasonswhy placing a laparoscopic adjustable band (LAGB) has almost currently become obsolete as primary bariatric treatment. A few studies have reported success rates in converting LAGB to sleeve gastrectomy when performed in a one-or a two-step procedure, [8,9] but overall, RYBG is the revisional procedure of choice. In most cases, conversion to RYGB can be performedin a one-step procedure.…”
Section: Motivation and Indication For Revisional Bariatric Surgerymentioning
confidence: 99%
“…Band erosions, pouch or esophageal dilatation, stapler line dehiscence, and band-related stenosis are reported anatomical complications, for which RYGB is considered as the preferred revisional procedure [14,15] although some report also acceptable results with conversion to sleeve gastrectomy. [8] As most patients suffer from reflux and established maladaptive eating, we can not support sleeve gastrectomy or pouchogastrostomy as revisional options after failed VBG.…”
Section: Revision Of Vbgmentioning
confidence: 99%